EVALUATION OF ANTIBIOTICS USED IN PATIENTS WITH ACUTE RESPIRATORY INFECTIONS IN A HOSPITAL - GINTING, PRICELLA AQWILLA; NASUTION, AZIZAH; KHAIRUNNISA, KHAIRUNNISA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study evaluated the use of antibiotics in the treatment of patients with acute respiratory infection (ARI) in the outpatients installation in Bunda Thamrin General Hospital, Medan. Methods: This prospective descriptive cohort study analyzed the use of antibiotics provided to patients with ARI using Indonesian universal health coverage known as Badan Penyelenggara Jaminan Sosial claims (n=130) in outpatients installations from March to May 2018. The characteristics of the patients were organized and descriptively analyzed in Excel and SPSS programs. The antibiotics provided were grouped according to the Anatomical Therapeutical Chemical code and class; then, the dosage form, defined daily dose (DDD) units, was converted into milligrams. DDD calculation was done by dividing the total DDD usage with the total number of patients. Results: Mean age of the patients was 32.12±10.579 years. The highest quantity of antibiotic use in DDD/1000 patients-day units was cefixime reaching 1,897.435 mg DDD KPRJ. Conclusions: Cefixime was the most widely available antibiotic for the treatment of ARI patients.